Müller glia activation by VEGF-antagonizing drugs: An in vitro study on rat primary retinal cultures. (April 2016) - Gaddini, Lucia; Varano, Monica; Matteucci, Andrea; Mallozzi, Cinzia; Villa, Marika; Pricci, Flavia; Malchiodi-Albedi, Fiorella
Abstract: The effects of the anti-Vascular Endothelial Growth Factor (VEGF) drugs ranibizumab and aflibercept were studied in Müller glia in primary mixed cultures from rat neonatal retina. Treatment with both agents induced activation of Müller glia, demonstrated by increased levels of Glial Fibrillary Acidic Protein. In addition, phosphorylated Extracellular-Regulated Kinase 1/2 (ERK 1/2) showed enhanced immunoreactivity in activated Müller glia. Treatment with aflibercept induced an increase in K + channel (Kir) 4.1 levels and both drugs upregulated Aquaporin 4 (AQP4) in activated Müller glia. The results show that VEGF-antagonizing drugs influence the homeostasis of Müller cells in primary retinal cultures, inducing an activated phenotype. Upregulation of Kir4.1 and AQP4 suggests that Müller glia activation following anti-VEGF drugs may not depict a detrimental gliotic reaction. Indeed, it could represent one of the mechanisms able to contribute to the therapeutic effects of these drugs, particularly in the presence of macular edema. Highlights: Ranibizumab and aflibercept increased GFAP expression in cultured Müller glia. Aflibercept upregulated Kir4.1. Both drugs upregulated Aquaporin 4. Anti-VEGF drugs induced a possibly beneficial Müller glia activation.